2018
DOI: 10.1016/j.amjcard.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Sustained 12 Month Benefit of Phrenic Nerve Stimulation for Central Sleep Apnea

Abstract: Transvenous phrenic nerve stimulation improved sleep metrics and quality of life after 6 months versus control in the remedē System Pivotal Trial. This analysis explored the effectiveness of phrenic nerve stimulation in patients with central sleep apnea after 12 months of therapy. Reproducibility of treatment effect was assessed in the former control group in whom the implanted device was initially inactive for the sixth month and subsequently activated when the randomized control assessments were complete. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
0
24
0
4
Order By: Relevance
“…10 PNS with the remed e system has been shown to improve symptoms and reduce central apneas and is currently indicated for patients diagnosed with moderateto-severe CSA. 11,12 Both sensing and pacing leads of the remed e system are programmable. The quadripolar left lead can be programmed in multipolar pacing configuration to deliver output between 0.1 and 10 mA at a pulse width of 60-300 microseconds.…”
Section: Discussionmentioning
confidence: 99%
“…10 PNS with the remed e system has been shown to improve symptoms and reduce central apneas and is currently indicated for patients diagnosed with moderateto-severe CSA. 11,12 Both sensing and pacing leads of the remed e system are programmable. The quadripolar left lead can be programmed in multipolar pacing configuration to deliver output between 0.1 and 10 mA at a pulse width of 60-300 microseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Możliwe jest zaprogramowanie stymulacji w trybie unipolarnym bądź bipolarnym. Wymuszone zaprogramowanym trybem stymulacji skurcze przepony przywracają regularność toru oddechowego, wykorzystując do tego wytworzone ujemne ciśnienie w klatce piersiowej, co zbliża mechanizm działania systemu remedē do fizjologicznego oddychania [20]. Stymulacja nerwu przeponowego zmniejsza lub znosi epizody bezdechu nocnego (ryc.…”
Section: Jak To Działa?unclassified
“…Średni czas zabiegu wyniósł 2,7 ± 0,8 h, a całkowity czas fluoroskopii 43,0 ± 22,5 min. Pozytywne efekty tego badania udokumentowano również w przedłużonej do 12 miesięcy obserwacji zarówno w zakresie parametrów oddechowych, jak i oceny jakości życia [20]. Ponadto stwierdzono niewielką, ale narastającą poprawę parametrów echokardiograficznych, między innymi LVEF, zarówno po 6 (wzrost z 38,6% ± 0.4 do 39,8 ± 0,4; p = 0,03), jak i po 12 miesiącach (wzrost z 38,6% ± 0,4 do 41,4 ± 0,4; p < 0,001).…”
Section: Badania Kliniczneunclassified
“…The IPG is a programmable device that provides an electrical stimulus to the left or right phrenic nerve and monitors the patient's respiration using transthoracic impedance. Stimulation of the left or right phrenic nerve causes the diaphragm to contract, thereby developing negative intrathoracic pressure and restoring regular breathing pattern …”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the left or right phrenic nerve causes the diaphragm to contract, thereby developing negative intrathoracic pressure and restoring regular breathing pattern. 10 Because of the lack of therapeutic options available for patients with CSA and the morbidity associated with the disease, phrenic nerve stimulation is an important treatment, especially for patients with concomitant heart failure. The remedē System Pivotal Trial demonstrated significant improvements in the number of sleep apnea events, sleep architecture, hypoxia, and arousals (all P < 0.001).…”
Section: Introductionmentioning
confidence: 99%